Studies on Carboniferous Insects From Commentry, France: Part V. The Genus Diaphanoptera and the Order Diaphanopterodea - F. M. Carpenter (Psyche: A Journal of Entomology)
This is the fifth in a series of studies based on the Carboniferous insects from the Commentry Basin, France. It consists of an analysis of the genus Diaphanoptera Brongniart and a discussion of the Order Diaphanopterodea, which was erected by Handlirsch in 1919 to receive the genus. In more recent years, there have been described other Carboniferous and Permian genera which, although previously placed in the Order Megasecoptera, now appear to belong to the Diaphanopterodea. This group of insects, apparently having a combination of palaeopterous and neopterous characteristics, presents one of the most intriguing and puzzling problems in the geological history of the insects. Our unsatisfactory knowledge of the Commentry fossils has added to the difficulties.